Estructura horizontal y volumen de las especies del bosque de la comunidad nativa Buen Jardín del Callaru, distrito del Yavarí – Loreto, Perú.2023 - Vilela Grandez, Virginia (2025)
The work was carried out in the forest of the Buen Jardín del Callaru native community, Yavarí district - Loreto Perú. A total of 80 trees were recorded, 05 commercial forest species and 05 botanical families, where the number of families is the same as the number of species. The Euphorbiaceae family with the highest number of trees (29), followed by the Cusiaseae family (23). Also, it is observed that the Catahua species reports the highest number of trees (29 trees), followed by the Caspi lizard (23); while a smaller number of trees contain Quinilla (03). The total volume was 910.42 m3 for the area (1771,98 Ha.) Lupuna (552,25 m3), Catahua (225,85 m3), contain the highest volume values; On the contrary, Moena (16,82 m3) and Lagarto caspi (8,57 m3) have a lower volume. The IVI shows that the Lupuna species (118,66%) is the ecologically important one in the forest of the Buen Jardín del Callarú native community, Yavarí district - Loreto Perú. Furthermore, it can be stated that one species reports little participation with less than 05% of IVI which is represented by the Caspi lizard (04,88%). The comparator value is p = 0,269, which is greater than the significance level α = 0,05 This leads to rejecting the alternative hypothesis and accepting the null hypothesis.